Diagnosis and Management of Bloodstream Infections With Rapid, Multiplexed Molecular Assays - Dunbar, Sherry A.; Gardner, Christopher; Das, Shubhagata (Frontiers in Cellular and Infection Microbiology, 2022)
Bloodstream infection is a major health concern, responsible for considerable morbidity and mortality worldwide. Rapid identification of the causative pathogen in the early stages of the disease allows clinicians to implement appropriate antibiotic therapy in a timelier manner. Prompt treatment with the correct antibiotic not only improves the chances of patient survival, but also significantly reduces the length of hospital stay and associated healthcare costs. Although culture has been the gold standard and most common method for diagnosis of bloodstream pathogens, it is being enhanced or supplanted with more advanced methods, including molecular tests that can reduce the turnaround time from several days to a few hours. In this article, we describe two rapid, molecular bloodstream infection panels that identify the most common pathogens and associated genetic determinants of antibiotic resistance – the Luminex® VERIGENE® Gram-Positive Blood Culture Test and the VERIGENE® Gram-Negative Blood Culture Test. We provide a comprehensive review of key publications illustrating the performance and clinical utility of these assays, demonstrating how genotypic tests can benefit diagnostic and antimicrobial stewardship efforts.